Nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst and preparation method and application thereof
Through the use of iron-nickel silicate/graphite-based carbon composite photofenton catalyst, the problem of low catalytic activity of the existing photofenton system has been solved, and efficient degradation of organic pollutants in water has been achieved.
Patent Information
- Application Number
- CN202411099077.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-08-12
AI Technical Summary
The existing photofenton system has low catalytic activity and is difficult to efficiently degrade organic pollutants in water.
Iron-nickel silicate/graphite-like carbon composite photofenton catalyst is used. This catalyst uses a composite of iron-nickel silicate with graphite-like carbon, and uses nickel elements and graphite-like carbon to promote Fe(III)/Fe(II) cycles to improve catalytic efficiency.
This catalyst can completely degrade 5-20 mg/L of phenolic pollutants or antibiotics within 7 minutes, significantly improving the photofenton degradation efficiency.
Smart Images

Figure CN118988324B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst, a preparation method of the catalyst, and an application of the catalyst. Background Art
[0002] With the rapid development of society and the intensification of industrialization, the problem of water pollution has become more and more serious. The organic pollutants discharged into the water are extremely harmful and difficult to degrade through traditional treatment methods. Homogeneous Fenton in advanced oxidation technology uses hydrogen peroxide (H2O2) and Fe(II) to produce highly oxidizing hydroxyl radicals (·OH) under acidic conditions, which degrade organic pollutants into low-toxic or non-toxic substances and can completely degrade organic pollutants. However, this reaction has the disadvantages of a small pH range, easy production of iron sludge, and low utilization of H2O2. Compared with traditional homogeneous Fenton, heterogeneous Fenton has a wider pH range of application and reduces the generation of iron sludge, but it still faces problems such as low efficiency of iron cycle (Fe(III) / Fe(II)).
[0003] At present, the heterogeneous photo-Fenton method has attracted much attention because it can promote iron cycling to a certain extent. The introduction of light can trigger the catalyst to produce reducing photogenerated electrons, realize the reduction conversion of Fe(III) to Fe(II), improve the utilization rate of H2O2, increase the production of ·OH, and help to degrade and remove organic pollutants in water. Iron-based catalysts are widely used in the field of photo-Fenton catalysis due to their excellent properties such as narrow band gap, low price, and wide light response range. However, most iron-based catalysts still have the limitations of high photogenerated electron-hole recombination rate and low photogenerated electron utilization, which limits their catalytic activity. Summary of the invention
[0004] The first object of the present invention is to provide a nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst, which solves the problem of low catalytic activity of the photo-Fenton system existing in the prior art.
[0005] The second object of the present invention is to provide a method for preparing the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst.
[0006] The third object of the present invention is to provide the use of nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst in photo-Fenton degradation of organic pollutants.
[0007] The first technical solution adopted by the present invention is that the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst includes nickel iron silicate and graphite-like carbon, and the graphite-like carbon is composited between the layers or on the surface of the nickel iron silicate.
[0008] The first technical solution of the present invention is also characterized in that the nickel iron silicate has a beidenite-like structure, and the structural formula of the nickel iron silicate is: Na(x+y) (Si 4-x Fe x )(Fe 2-y Ni y ) 10 (OH)2·nH2O, where 0.2≤x≤0.4, 0.1≤y≤0.3, 0.3≤n≤10.
[0009] The second technical solution adopted by the present invention is a method for preparing a nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst, which is specifically implemented according to the following steps:
[0010] Step 1, adding sodium hydroxide, sodium bicarbonate and sodium silicate to deionized water in sequence to prepare an alkaline solution, then adding ferric chloride hexahydrate and nickel chloride hexahydrate to the deionized water to prepare a metal salt solution, dropping the metal salt solution into the alkaline solution, and adjusting the pH to neutral with hydrochloric acid to obtain a mixed solution;
[0011] Step 2, transferring the mixed solution to a reactor for hydrothermal reaction, washing the reaction product with deionized water after cooling, freeze-drying and grinding it into powder to obtain nickel iron silicate nanosheets;
[0012] Step 3, dispersing nickel iron silicate nanosheets in deionized water, then adding glucose to obtain a mixed solution, transferring the mixed solution after ultrasonication and stirring to a reactor for hydrothermal reaction, washing the reaction product with deionized water and anhydrous ethanol after cooling, and grinding it into powder after freeze-drying;
[0013] Step 4: calcining the powder obtained in step 3 under a nitrogen atmosphere to obtain a nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst.
[0014] The second technical solution of the present invention is also characterized in that:
[0015] In step 1, the deionized water in the alkaline solution is 40mL-60mL, the molar amount of sodium hydroxide is 35mmol-55mmol, the molar amount of sodium bicarbonate is 10mmol-18mmol, the molar amount of sodium silicate is 6mmol-10mmol, the deionized water in the metal salt solution is 8mL-12mL, the molar amount of ferric chloride hexahydrate is 4.5mmol-5.5mmol, and the molar amount of nickel chloride hexahydrate is 1.5mmol-4.5mmol.
[0016] The temperature of the hydrothermal reaction in step 2 is 170° C.-190° C., the reaction time is 60 h-80 h, and the freeze drying is 18 h-30 h.
[0017] In the mixed solution of step 3, deionized water is 15 mL-25 mL, nickel iron silicate nanosheets are 0.4 g-0.8 g, the molar amount of glucose is 3 mmol-10 mmol, the hydrothermal reaction temperature is 170° C.-190° C., the reaction time is 2 h-4 h, and the freeze drying is 18 h-30 h.
[0018] The specific parameters of calcination in step 4 are: heating to 400-600°C at a heating rate of 5°C / min-10°C / min, and then keeping the temperature for 2h-5h.
[0019] The nickel iron silicate nanosheets have a thickness of 5nm-10nm, a lateral size of 200nm-400nm, and a specific surface area of 150m 2 / g-190m 2 / g; in the catalyst obtained after calcination in step 4, the mass fraction of graphite-like carbon in the catalyst is 15%-25%.
[0020] The third technical solution adopted by the present invention is the use of nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst in photo-Fenton degradation of organic pollutants.
[0021] The third technical solution of the present invention is also characterized in that:
[0022] Organic pollutants are phenolic pollutants or antibiotics.
[0023] The beneficial effects of the present invention are:
[0024] The nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst of the present invention has strong visible light absorption ability and narrow bandgap; the large specific surface area of the iron-based silicate is conducive to the contact between the catalyst and the organic pollutants, and can provide more active sites to participate in the reaction; the nickel element in the silicate layer can serve as an electron transfer "medium" to accelerate the electron transmission in the photo-Fenton reaction; the graphite-like carbon can promote the separation of photogenerated electrons and holes and improve the utilization efficiency of photogenerated electrons. The nickel element and the graphite-like carbon synergistically promote the Fe(III) / Fe(II) cycle, improve the catalytic efficiency, and solve the problem of low catalytic activity of the photo-Fenton system existing in the prior art. The photo-Fenton degradation of organic pollutants has excellent performance, and 5-20 mg / L of organic pollutants (phenolic pollutants, antibiotics) can be completely degraded within 7 minutes. The preparation method of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst of the present invention has cheap and easy-to-obtain raw materials and low preparation cost; the preparation process is simple and controllable. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is an X-ray diffraction spectrum of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst of the present invention;
[0026] Figure 2It is a scanning electron microscope image of the nickel iron silicate nanosheet and the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst in the present invention;
[0027] Figure 3 It is the UV-visible diffuse reflectance image of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst and nickel iron silicate nanosheets of the present invention;
[0028] Figure 4 The figure is a photo-Fenton degradation effect diagram of sulfamethoxazole, carbamazepine and phenol by the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst of the present invention. DETAILED DESCRIPTION
[0029] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0030] The preparation method of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:
[0031] Step 1, adding sodium hydroxide, sodium bicarbonate and sodium silicate to deionized water in sequence to prepare an alkaline solution, then adding ferric chloride hexahydrate and nickel chloride hexahydrate to the deionized water to prepare a metal salt solution, slowly dropping the metal salt solution into the alkaline solution, and adjusting the pH to neutral with hydrochloric acid to obtain a mixed solution;
[0032] In step 1, the deionized water in the alkaline solution is 40mL-60mL, the molar amount of sodium hydroxide is 35mmol-55mmol, the molar amount of sodium bicarbonate is 10mmol-18mmol, the molar amount of sodium silicate is 6mmol-10mmol, the deionized water in the metal salt solution is 8mL-12mL, the molar amount of ferric chloride hexahydrate is 4.5mmol-5.5mmol, and the molar amount of nickel chloride hexahydrate is 1.5mmol-4.5mmol;
[0033] Step 2, transferring the mixed solution to a reactor for hydrothermal reaction, washing the reaction product with deionized water for multiple times after cooling, freeze-drying and grinding into powder to obtain nickel iron silicate nanosheets;
[0034] The structure of nickel iron silicate nanosheets is beidenite-like structure. The thickness of nickel iron silicate nanosheets is 5nm-10nm, the lateral size is 200nm-400nm, and the specific surface area is 150m 2 / g-190m 2 / g;
[0035] The temperature of the hydrothermal reaction in step 2 is 170°C-190°C, the reaction time is 60h-80h, and the freeze drying is 18h-30h;
[0036] Step 3, dispersing nickel iron silicate nanosheets in deionized water, then adding glucose to obtain a mixed solution, transferring the mixed solution after ultrasonication and stirring to a reactor for hydrothermal reaction, washing the reaction product with deionized water and anhydrous ethanol for multiple times after cooling, and grinding it into powder after freeze-drying;
[0037] In the mixed solution of step 3, the amount of deionized water is 15 mL-25 mL, the amount of nickel iron silicate nanosheets is 0.4 g-0.8 g, the molar amount of glucose is 3 mmol-10 mmol, the hydrothermal reaction temperature is 170° C.-190° C., the reaction time is 2 h-4 h, and the freeze drying is 18 h-30 h;
[0038] Step 4, calcining the powder obtained in step 3 under a nitrogen atmosphere to obtain a nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst;
[0039] The specific parameters of calcination in step 4 are: heating at a rate of 5°C / min-10°C / min to 400°C-600°C, and then keeping the temperature for 2h-5h;
[0040] In the catalyst obtained after calcination in step 4, the mass fraction of graphite-like carbon in the catalyst is 15%-25%.
[0041] The nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst prepared by the invention comprises nickel iron silicate and graphite-like carbon, wherein the graphite-like carbon is composited between the layers or on the surface of the nickel iron silicate.
[0042] Example 1
[0043] The preparation method of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:
[0044] Step 1, add 45mmol of sodium hydroxide, 14mmol of sodium bicarbonate and 8mmol of sodium silicate to 50mL of deionized water in sequence to prepare an alkaline solution, then add 5mmol of ferric chloride hexahydrate and 3mmol of nickel chloride hexahydrate to 10mL of deionized water to prepare a metal salt solution, slowly dropwise add the metal salt solution to the alkaline solution, stir well, adjust the pH of the solution to 7 with hydrochloric acid, and stir well to obtain a mixed solution;
[0045] Step 2: Transfer the mixed solution to a reactor, perform a hydrothermal reaction at 180°C for 72 hours, cool the reaction product, wash the reaction product with deionized water, freeze-dry for 24 hours, and grind it into powder to obtain nickel iron silicate nanosheets. The nanosheets have a thickness of about 8 nm, a lateral size of about 280 nm, and a specific surface area of 170 m 2 / g;
[0046] Step 3, first add 0.6 g of nickel iron silicate nanosheets to 20 mL of deionized water, stir and disperse thoroughly, then add 6 mmol of glucose to obtain a mixed solution, transfer the mixed solution after ultrasonication and stirring to a reactor, perform hydrothermal reaction at a temperature of 180° C. for 3 h, cool to obtain a reaction product, wash the reaction product with deionized water and anhydrous ethanol, freeze-dry for 24 h, and then grind into powder;
[0047] Step 4: The powder obtained in step 3 is heated to 500° C. at a heating rate of 10° C. / min, and calcined for 4 h in a nitrogen atmosphere to obtain a nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst.
[0048] The X-ray diffraction spectrum of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst obtained in Example 1 is shown in Figure 1 The XRD spectrum shows characteristic diffraction peaks (001), (100), (110) and (300) crystal planes of nickel-iron silicate layered structure that can be characterized as beidenite-like structure, and a weak diffraction peak appears at around 26.3°, which belongs to the (002) crystal plane of graphite-like carbon.
[0049] The nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst obtained in Example 1 was used to degrade sulfamethoxazole: a 300 W xenon lamp (λ>422 nm) was used as the excitation light source, the reaction temperature was 25°C, the concentration of sulfamethoxazole in the aqueous solution was 10 mg / L, the concentration of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst in the reaction system was 200 mg / L, the concentration of hydrogen peroxide in the aqueous solution was 10 mmol / L, the mixed solution of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst and sulfamethoxazole was kept in the dark for 30 min until the adsorption-desorption equilibrium was reached, the light source was turned on, and the irradiation amount of the light source per unit area on the surface of the solution was 610 mW / cm 2 After stirring for 7 minutes, the degradation rate of sulfamethoxazole was measured to be 100%.
[0050] Example 2
[0051] The preparation method of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:
[0052] Step 1, add 35 mmol of sodium hydroxide, 10 mmol of sodium bicarbonate and 6 mmol of sodium silicate to 40 mL of deionized water in sequence to prepare an alkaline solution, then add 4.5 mmol of ferric chloride hexahydrate and 1.5 mmol of nickel chloride hexahydrate to 8 mL of deionized water to prepare a metal salt solution, slowly dropwise add the metal salt solution to the alkaline solution, stir well, adjust the pH of the solution to 7 with hydrochloric acid, and stir well to obtain a mixed solution;
[0053] Step 2: Transfer the mixed solution to a reactor, perform a hydrothermal reaction at 170°C for 80 hours, cool the reaction product, wash the reaction product with deionized water, freeze-dry for 18 hours, and grind it into powder to obtain nickel iron silicate nanosheets. The nanosheets have a thickness of about 5 nm, a lateral size of about 200 nm, and a specific surface area of 150 m 2 / g;
[0054] Step 3, first add 0.4 g of nickel iron silicate nanosheets to 15 mL of deionized water, stir and disperse thoroughly, then add 3 mmol of glucose to obtain a mixed solution, transfer the mixed solution after ultrasonication and stirring to a reactor, perform hydrothermal reaction at a temperature of 170° C. for 4 h, cool to obtain a reaction product, wash the reaction product with deionized water and anhydrous ethanol, freeze-dry for 18 h, and then grind into powder;
[0055] Step 4: The powder obtained in step 3 is heated to 400° C. at a heating rate of 7° C. / min, and calcined for 5 h in a nitrogen atmosphere to obtain a nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst.
[0056] The scanning electron microscope images of the nickel iron silicate nanosheets and the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst obtained in Example 2 are shown in Figure 2 ,from Figure 2 a Scanning electron microscopy image shows that the nickel iron silicate nanosheets present a two-dimensional cross-linked porous network structure, and the edges of the sheets are curled. Figure 2 b Scanning electron microscopy image shows that after glucose modification and calcination, the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst still maintains the morphology of two-dimensional nanosheets, but the size of the nanosheets becomes smaller and the specific surface area increases.
[0057] The nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst obtained in Example 2 was used to degrade carbamazepine: a 300 W xenon lamp (λ>422 nm) was used as the excitation light source, the reaction temperature was 25° C., the concentration of carbamazepine in the aqueous solution was 10 mg / L, the concentration of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst in the reaction system was 200 mg / L, the concentration of hydrogen peroxide in the aqueous solution was 10 mmol / L, the mixed solution of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst and carbamazepine was kept in the dark for 30 min in advance until the adsorption-desorption equilibrium was reached, the light source was turned on, and the irradiation amount of the light source per unit area on the surface of the solution was 610 mW / cm 2 After stirring for 7 minutes, the degradation rate of carbamazepine was measured to be 100%.
[0058] Example 3
[0059] The preparation method of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:
[0060] Step 1, add 55 mmol of sodium hydroxide, 18 mmol of sodium bicarbonate and 10 mmol of sodium silicate to 60 mL of deionized water to prepare an alkaline solution, then add 5.5 mmol of ferric chloride hexahydrate and 4.5 mmol of nickel chloride hexahydrate to 12 mL of deionized water to prepare a metal salt solution, slowly dropwise add the metal salt solution to the alkaline solution, stir well, adjust the pH of the solution to 7 with hydrochloric acid, and stir well to obtain a mixed solution;
[0061] Step 2: Transfer the mixed solution to a reactor, perform a hydrothermal reaction at 190°C for 60 hours, cool the reaction product, wash the reaction product with deionized water, freeze-dry for 30 hours, and grind it into powder to obtain nickel iron silicate nanosheets. The nanosheets have a thickness of about 10 nm, a lateral size of about 400 nm, and a specific surface area of 190 m 2 / g;
[0062] Step 3, first add 0.8 g of nickel iron silicate nanosheets to 25 mL of deionized water, stir and disperse thoroughly, then add 10 mmol of glucose to obtain a mixed solution, transfer the mixed solution after ultrasonication and stirring to a reactor, perform hydrothermal reaction at a temperature of 190° C. for 2 h, cool to obtain a reaction product, wash the reaction product with deionized water and anhydrous ethanol, freeze-dry for 30 h, and then grind into powder;
[0063] Step 4: The powder obtained in step 3 is heated to 600° C. at a heating rate of 5° C. / min, and calcined for 2 h in a nitrogen atmosphere to obtain a nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst.
[0064] The UV-visible diffuse reflectance images of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst and nickel iron silicate nanosheets obtained in Example 3 are shown in FIG. Figure 3 , it can be seen that the nickel iron silicate / graphite-like carbon composite material has a strong light absorption ability in the range of 200nm-800nm.
[0065] The nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst obtained in Example 3 was used to degrade phenol: a 300 W xenon lamp (λ>422 nm) was used as the excitation light source, the reaction temperature was 25° C., the concentration of phenol in the aqueous solution was 10 mg / L, the concentration of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst in the reaction system was 200 mg / L, the concentration of hydrogen peroxide in the aqueous solution was 10 mmol / L, the mixed solution of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst and phenol was kept in the dark for 30 min until the adsorption-desorption equilibrium was reached, the light source was turned on, and the irradiation amount of the light source per unit area on the solution surface was 610 mW / cm 2 After stirring and reacting for 7 minutes, the phenol degradation rate was measured to be 100%.
[0066] The photo-Fenton degradation effects of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalysts obtained in Examples 1-3 on sulfamethoxazole, carbamazepine and phenol are shown in Figure 4 It can be seen that the degradation rate of pollutants by nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst can reach 100% within 7 minutes.
[0067] The nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst of the present invention has strong visible light absorption capability and narrow bandgap; the large specific surface area of the iron-based silicate is conducive to the contact between the catalyst and the organic pollutants, and can provide more active sites to participate in the reaction; the nickel element in the silicate layer can serve as an electron transfer "medium" to accelerate the electron transmission in the photo-Fenton reaction; the graphite-like carbon can promote the separation of photogenerated electrons and holes, and improve the utilization efficiency of photogenerated electrons. The nickel element and the graphite-like carbon synergistically promote the Fe(III) / Fe(II) cycle, improve the catalytic efficiency, and solve the problem of low catalytic activity of the photo-Fenton system existing in the prior art. The photo-Fenton degradation of organic pollutants has excellent performance, and within 7 minutes, 5mg / L-20mg / L of organic pollutants (phenolic pollutants, antibiotics) can be completely degraded.
Claims
1. Nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst, characterized in that: It comprises nickel iron silicate and graphite-like carbon, wherein the graphite-like carbon is compounded between the layers or on the surface of the nickel iron silicate; The nickel iron silicate is a beidenite-like structure, and the structural formula of the nickel iron silicate is: Na (x+y) (Si 4-x Fe x )(Fe 2-y Ni y ) 10 (OH)2·nH2O, where 0.2≤x≤0.4, 0.1≤y≤0.3, 0.3≤n≤10; The preparation method of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst is specifically implemented according to the following steps: Step 1, adding sodium hydroxide, sodium bicarbonate and sodium silicate to deionized water in sequence to prepare an alkaline solution, then adding ferric chloride hexahydrate and nickel chloride hexahydrate to the deionized water to prepare a metal salt solution, dropping the metal salt solution into the alkaline solution, and adjusting the pH to neutral with hydrochloric acid to obtain a mixed solution; Step 2, transferring the mixed solution to a reactor for hydrothermal reaction, washing the reaction product with deionized water after cooling, freeze-drying and grinding it into powder to obtain nickel iron silicate nanosheets; Step 3, dispersing nickel iron silicate nanosheets in deionized water, then adding glucose to obtain a mixed solution, and then transferring the mixed solution after ultrasonication and stirring to a reactor for hydrothermal reaction, the hydrothermal reaction temperature is 170°C-190°C, the reaction time is 2h-4h, and after cooling, the reaction product is washed with deionized water and anhydrous ethanol, freeze-dried and ground into powder; Step 4, calcining the powder obtained in step 3 under a nitrogen atmosphere to obtain a nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst; The specific parameters of the calcination in step 4 are: heating to 400°C-600°C at a heating rate of 5°C / min-10°C / min, and then keeping the temperature for 2h-5h.
2. The nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst according to claim 1, characterized in that: In the step 1, the deionized water in the alkaline solution is 40mL-60mL, the sodium hydroxide is 35mmol-55mmol, the sodium bicarbonate is 10mmol-18mmol, the sodium silicate is 6mmol-10mmol, the deionized water in the metal salt solution is 8mL-12mL, the ferric chloride hexahydrate is 4.5mmol-5.5mmol, and the nickel chloride hexahydrate is 1.5mmol-4.5mmol.
3. The nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step 2 is 170° C.-190° C., the reaction time is 60 h-80 h, and the freeze drying in step 2 is 18 h-30 h.
4. The nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst according to claim 1, characterized in that: The mixed solution in step 3 contains 15 mL-25 mL of deionized water, 0.4 g-0.8 g of nickel iron silicate nanosheets, and 3 mmol-10 mmol of glucose. The freeze-drying step in step 3 is performed for 18 h-30 h.
5. The nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst according to claim 1, characterized in that: The nickel iron silicate nanosheet has a thickness of 5nm-10nm, a lateral size of 200nm-400nm, and a specific surface area of 150m 2 / g -190m 2 / g; the mass percentage of graphite-like carbon in the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst is 15%-25%.
6. Use of the nickel iron silicate / graphite-like carbon composite photo-Fenton catalyst according to any one of claims 1 to 5 in photo-Fenton degradation of organic pollutants.
7. The use according to claim 6, characterized in that: The organic pollutants are phenolic pollutants or antibiotics.
Citation Information
Patent Citations
Preparation method of carbon-doped iron oxychloride composite material
CN115770593A
Visible-light-responsive layered ferric silicate photo-Fenton catalyst, preparation method and application of visible-light-responsive layered ferric silicate photo-Fenton catalyst
CN116618056A
Double-metal layered silicate catalyst based on natural zeolite and application of double-metal layered silicate catalyst
CN116726977A